Assessing the methodological quality of quality-of-life analyses in first-line non-small cell lung cancer trials: A systematic review. (August 2022) - Waisberg, Federico; Lopez, Carlos; Enrico, Diego; Rodriguez, Andrés; Hirsch, Ian; Burton, Jeannette; Mandó, Pablo; Martin, Claudio; Chacón, Matias; Seetharamu, Nagashree
Abstract: Background: Non-cytotoxic therapy has changed the treatment paradigm for advanced non-small cell lung cancer (NSCLC) patients. With unique mechanisms of action, these agents have decidedly improved survival and have demonstrated an improved toxicity profile. However, the real-life experience of the patient, which is commonly assessed by health-related quality of life (HRQoL) measurement, is not clearly established with this new generation of lung cancer treatments. The heterogeneity created by specific patient subgroups and different therapeutics calls for a tailored-approach to analyzing patient-reported outcomes. The objective of this systematic review was to assess the methodological quality of HRQoL analysis in Randomized Clinical Trials (RCTs) involving biologic agents to treat NSCLC. Methods: A systematic literature search was performed using Medline, Embase, and Web of Science databases to identify NSCLC RCTs published between January 1st, 2000 and January 1st, 2020 reporting HRQoL measures. Only RCTs that both enrolled previously untreated patients with advanced NSCLC and had HRQoL analysis were included. Results: 4203 abstracts were screened, of which only 85 RCTs met inclusion and exclusion criteria for analysis. The most applied HRQoL assessment tools were the EORTC-QLQ-C30 (47, 55.3 %), and EORTC-QLQ-LC13 (35, 41.2 %). The median number of verified CONSORT-PRO Extension criteria in the included trials was 3, and only in 10 (11.8 %) trials were all criteria well-documented. Notably, only 21 (24.7 %) RCTs performed subgroup analyses to specifically evaluate HRQoL in different patient populations. Conclusion: QoL reporting in clinical trials is inconsistent and the quality of QoL measures adopted in a majority of trials is suboptimal. Considering the fact that NSCLC is a biologically diverse disease and that the treatments differ based on patient and tumor-specifics, efforts should be pursued to tailor QoL measures for different subsets of this patient population in addition to mandating QoL reporting in clinical trials. We believe that this is necessary to understand the real-life experience of lung cancer patients in the era of personalized medicine. Graphical Abstract: ga1 Highlights: Only two HRQoL instruments were used in 31 % of 85 clinical trials to evaluate PROs. 12 % of the included trials met all CONSORT Extension Criteria for PRO reporting. Subgroup analysis to evaluate PROs was performed only in 24.7 % of the studies. Patient heterogeneity supports the incorporation of tailored tools for PRO analysis.